2012
DOI: 10.4028/www.scientific.net/kem.512-515.1367
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Piezoelectric Properties of CaBi<sub>2</sub>Nb<sub>2</sub>O<sub>9</sub> with Eu Modification and Templated Grain Growth

Abstract: Calcium bismuth niobate (CaBi2Nb2O9, CBN) is a high Curie temperature (Tc) piezoelectric material, however, their piezoelectric properties are very poor. In order to improve the piezoelectric performance of CBN, the Eu modification and texture method (templated grain growth, TGG) were applied in this material system. The piezoelectric properties of CBN ceramics were significantly enhanced by Eu modification. The 5mol% Eu dopants in CBN ceramics have a higher piezoelectric constant and higher Tc (d33=12.8pC/N, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…Obviously, below 800℃, all the W/Cu co‐doped specimens exhibited resistivity that was superior to that of the pure specimen, and this indicates that W/Cu doping effectively promotes resistivity. A comparison of d 33 and ρ (@600℃) obtained in this study with those of reported CBN ceramics is presented in Figure 8B 7,9,11,12,16,17,29,36‐40 . Apparently, high piezoelectricity and high‐temperature resistivity are simultaneously achieved in this study, showing that the material has advantages for potential high‐temperature piezoelectric application.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…Obviously, below 800℃, all the W/Cu co‐doped specimens exhibited resistivity that was superior to that of the pure specimen, and this indicates that W/Cu doping effectively promotes resistivity. A comparison of d 33 and ρ (@600℃) obtained in this study with those of reported CBN ceramics is presented in Figure 8B 7,9,11,12,16,17,29,36‐40 . Apparently, high piezoelectricity and high‐temperature resistivity are simultaneously achieved in this study, showing that the material has advantages for potential high‐temperature piezoelectric application.…”
Section: Resultssupporting
confidence: 57%
“…A comparison of d 33 and ρ (@600℃) obtained in this study with those of reported CBN ceramics is presented in Figure 8B. 7,9,11,12,16,17,29,[36][37][38][39][40] Apparently, high piezoelectricity and high-temperature resistivity are simultaneously achieved in this study, showing that the material has advantages for potential high-temperature piezoelectric application.…”
Section: Raw Materialsmentioning
confidence: 51%
“…These undesirable factors make CBN unsuitable for high‐temperature applications. In order to overcome these drawbacks of CBN ceramic materials, several approaches have been developed to improve the electrical properties, such as compositions adjusting and grain orientation techniques 12–14 . Compositions adjusting by elements modifications is considered an effective approach to tailor the crystalline structure and microscopic morphology and thereby can effectively improve the piezoelectric and electrical properties of CBN 15–18 .…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome these drawbacks of CBN ceramic materials, several approaches have been developed to improve the electrical properties, such as compositions adjusting and grain orientation techniques. [12][13][14] Compositions adjusting by elements modifications is considered an effective approach to tailor the crystalline structure and microscopic morphology and thereby can effectively improve the piezoelectric and electrical properties of CBN. [15][16][17][18] For example, the (Li, Ce, Y)-modified CBN exhibits enhanced piezoelectric performance with a piezoelectric coefficient d 33 of 16.3 pC/N because of the octahedral tilt, and it also exhibits enhanced dc electrical resistivity, larger by one order of magnitude than unmodified CBN.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, CBN ceramics exhibit very low piezoelectric properties with a piezoelectric constant d 33 of ∼5 pC N −1 , as a result of the limitation of domain switching by the layered crystal structure. Therefore, different preparation methods have been adopted to enhance the piezoelectric properties of CBN-based ceramics [14][15][16][17][18][19][20][21][22][23]. Composition adjustment and grain-orientation techniques can improve the piezoelectric properties of CBN, and a piezoelectric constant d 33 of ∼20 pC N −1 can be achieved by grain orientation techniques or composition adjustment [22][23][24].…”
Section: Introductionmentioning
confidence: 99%